Target Domains of Ayam 'Chiken' in Indonesian Proverbs - Wijana, I Dewa Putu (Kajian Bahasa dan Sastra (KABASTRA), 2022)
This paper aims at describing the various target domains possibly referred by the source domain ayam 'chiken' found in Indonesian proverbs. By observing data mainly collected from Indonesian proverb book, it is found that ayam 'chiken' as one of the most popular animals raised by Indonesian people can be exploited to metaphorically resemble various source domains. Those are from the most common to the least, are i.e human state, human character, problem, luck, and truth and falsity.